Health Sector Efficiency Across Indian States Using Stochastic Frontier Analysis - Dar, Khursheed Hussain; Bhat, Tariq Ahmad (Asian Development Policy Review, 2017)
Health and education are the two most influential variables in determining the human resource development. Human resource development is the backbone of human capital, which in turn is the main driver of the economic growth and development. India has a relatively poor health outcomes compared with the economies of its size because the success in its economic parameters has not been replicated in its health outcomes. The two main reasons responsible for this the low public health spending and poor resource use efficiency. There is a skewed progress in uplifting the health outcomes across Indian States. In some States health outcomes are improving fast while in others the health outcomes have failed to respond even after enhancing the investments hence reflecting their resource use inefficiency. This paper analyses the resource use efficiency in health sector across Indian States using Stochastic Frontier Approach (SFA).